Association of preoperative spirometry with cardiopulmonary fitness and postoperative outcomes in surgical patients: A multicentre prospective cohort study - Ashwin Sankar; Kevin E. Thorpe; Andrea S. Gershon; John T. Granton; Duminda N. Wijeysundera (EClinicalMedicine, 2020)
Background: Preoperative spirometry and cardiopulmonary exercise testing (CPET) may stratify risk for respiratory complications. This secondary analysis of the Measurement of Exercise Tolerance before Surgery (METS) study examined whether CPET performance (i.e., cardiopulmonary fitness) confounds associations of spirometry with outcomes. Methods: The analysis included 1200 participants having major non-cardiac surgery at 25 hospitals in Canada, Australia, New Zealand and UK. Forced expiratory volume in 1 s (FEV1), and ratio of FEV1 to forced vital capacity (FVC) were measured during preoperative spirometry, and peak oxygen consumption and ventilatory efficiency during preoperative CPET. Outcomes were respiratory morbidity (Postoperative Morbidity Survey) and pulmonary complications (pneumonia or respiratory failure). We used multivariable logistic regression models to estimate associations of FEV1 with outcomes after adjustment for risk factors and either peak oxygen consumption or ventilatory efficiency. Findings: 128 participants (11%) developed respiratory morbidity, and 48 (4%) developed pulmonary complications. There was no strong evidence that FEV1 predicted respiratory morbidity after adjustment for peak oxygen consumption (p = 0·80) or ventilatory efficiency (p = 0·76), or FEV1 predicted pulmonary complications after adjustment for ventilatory efficiency (p = 0·37). Peak oxygen consumption (odds ratio 0·66 per 5 mL/kg/min increase; 95% CI, 0·54–0·82) was associated with respiratory morbidity. Ventilatory efficiency was associated with respiratory morbidity (p = 0·04) and pulmonary complications (p = 0·02). Peak oxygen consumption also confounded the association between FEV1 and respiratory morbidity. Interpretation: After accounting for fitness and clinical factors, FEV1 was not strongly predictive of respiratory complications. Prior associations between FEV1 and respiratory morbidity may be explained by confounding by peak oxygen consumption. Funding: Canadian Institutes of Health Research, Heart and Stroke Foundation of Canada, Ontario Ministry of Health and Long-Term Care, Ontario Ministry of Research, Innovation and Science, UK National Institute of Academic Anaesthesia, UK Clinical Research Collaboration, Australian and New Zealand College of Anaesthetists, and Monash University.